Silver‐ and Silver–Hydrogen‐Related Defects in Silicon. Issue 23 (29th July 2021) - Gwozdz, Katarzyna; Kolkovsky, Vladimir
Abstract : Herein, the electrical and structural properties of Ag‐ and AgH‐related defects in n‐ and p‐type Si are reinvestigated using conventional deep‐level transient spectroscopy (DLTS) and high‐resolution Laplace DLTS. It is evidenced that a peak corresponding to substitutional Ag does not always appear in as‐grown Si and additional heat treatments are necessary to observe this defect. Several AgH‐related peaks, which were not previously reported in the literature, are observed in hydrogenated n‐ and p‐type Si. The electrical properties of these defects are determined and their origin is discussed. By using high‐resolution Laplace DLTS, the depth profiles of AgH‐related defects previously assigned to AgS H and AgS H2 are analyzed, and their assignments are questioned. Abstract : The electrical and structural properties of Ag and AgH‐related complexes are reinvestigated by deep‐level transient spectroscopy (DLTS) and Laplace DLTS. Analyzing depth profiles of the defects, the previous assignment of E2 and E3 to different charge states of AgS H is questioned. Should be edited as several novel DLTS peaks in as‐grown samples and after their hydrogenation are appeared. Their origin is also discussed.